AN ANALYSIS OF FISHBEIN MULTIATRIBUTE ATTITUDE OF AWAI NA SHRIMP PASTE PRODUCTS AND INDOFOOD SHRIMP PASTE PRODUCTS - Safrizal Safrizal; Rulianda Purnomo Wibowo; Tavi Supriana (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to analyze consumer attitudes towards Awai Na shrimp paste products and Indofood shrimp paste products in Langsa City, to analyze consumer ratings of the attributes of Awai Na shrimp paste products and Indofood shrimp paste products in Langsa City, and to analyze consumer confidence in these attributes on Awai Na shrimp paste products and on Indofood shrimp paste products in Langsa City. The analytical method used is the Fishbein Multi Attribute Attitude Model. The multi-attribute attitude model explains that consumer attitudes towards an attitude object (product or brand) are largely determined by consumer attitudes towards the evaluated attributes. The shrimp paste attributes used in this study consisted of: price, taste, aroma, color, texture, and size. The results of this study indicate that based on the Fishbein score, the total score for Awai Na shrimp paste products (3.142) is greater than Indofood shrimp paste products (0.999). This means that consumers in Langsa City prefer Awai Na shrimp paste products to Indofood shrimp paste products for consumption. Consumers prefer Awai Na shrimp paste over Indofood shrimp paste, because consumers perceive all attributes of Awai Na shrimp paste as better than Indofood's shrimp paste attributes. Consumers' evaluations of the Awai Na and Indofood shrimp paste are influenced by the consumer's experience in consuming the Awai Na and Indofood shrimp paste.